2005
DOI: 10.1063/1.1849833
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of TiN porous templates on the reduction of threading dislocations in GaN overgrowth by organometallic vapor-phase epitaxy

Abstract: We report on the reduction of threading dislocations in GaN overlayers grown by organometallic vapor phase epitaxy on micro-porous TiN networks. These networks were obtained by in situ annealing of thin Ti layers deposited in a metalization chamber, on the ͑0001͒ face of GaN templates. Observations by transmission electron microscopy indicate dislocation reduction by factors of up to 10 in GaN layers grown on TiN networks compared with the control GaN. X-ray diffraction shows that GaN grown on the TiN network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…In other words, narrower (0 0 2) and (1 0 2) XRD peaks were achieved for the AlGaN/GaN epitaxial layers grown on 11-tilt sapphire substrate (i.e., sample A). It was known that the symmetrical XRD FWHM was most sensitive to the screw and/or mixed dislocations, while the asymmetrical XRD FWHM was related to the other dislocation such as edge dislocation [15,16]. Therefore, a narrower peak width of symmetrical and asymmetrical HRXRD rocking curves suggests that the crystalline quality of AlGaN/GaN films grown on vicinal-cut sapphire substrate is better than that of the same epi-structure grown on c-axis-oriented sapphire substrate.…”
Section: Resultsmentioning
confidence: 91%
“…In other words, narrower (0 0 2) and (1 0 2) XRD peaks were achieved for the AlGaN/GaN epitaxial layers grown on 11-tilt sapphire substrate (i.e., sample A). It was known that the symmetrical XRD FWHM was most sensitive to the screw and/or mixed dislocations, while the asymmetrical XRD FWHM was related to the other dislocation such as edge dislocation [15,16]. Therefore, a narrower peak width of symmetrical and asymmetrical HRXRD rocking curves suggests that the crystalline quality of AlGaN/GaN films grown on vicinal-cut sapphire substrate is better than that of the same epi-structure grown on c-axis-oriented sapphire substrate.…”
Section: Resultsmentioning
confidence: 91%
“…The intensity of AlGaN (0 0 2) for sample B is much stronger than that of sample A. Previously, it has been demonstrated that the X-ray rocking curve for the symmetric (0 0 2)-reflecting plane is related to screw and mixed dislocations, whereas the X-ray rocking curve for the asymmetric (1 0 2)-reflecting plane is directly influenced by all threading dislocations, including edge dislocations [12][13][14]. We believe that the improved crystal quality is related to the alleviation of lattice mismatch between AlGaN and the underneath sapphire substrate.…”
Section: Resultsmentioning
confidence: 95%
“…As we know, the strain along the growth direction is found to be tensile as elasticity theory predicts in the case of biaxial stress [15][16][17][18]. By comparison to the number of V-shaped pits, more tensile strain can be relieved in the condition of more V-shaped pits on the surface of Sample B.…”
Section: Raman Scatteringmentioning
confidence: 82%